Basiskomponenten der Persönlichkeit - Ertel, Suitbert (Universitätsverlag Göttingen, 2011)
Thurstone's principle of simple structure is rejected and replaced by its converse, the principle of complex structure. Varimax, the popular simple structure rotation of factors, is replaced by varimin, a novel procedure taking account of the complexity of investigated variables (s. Ertel, 2011). An exploratory factor analysis of a similarity matrix of 16 kinship terms showed that expected semantic features (sex, generation, nuclear family, lineality) manifest themselves by varimin rotation,while distorted clusters of kinship terms are obtained by varimax rotation. Varimin rotation was also applied to five PCA-factors obtained from 30 facet variables of NEO-PI-R (Ostendorf & Angleitner, 2004). As expected, variminrotated factors do not replicate the Big-Five factors neuroticism, extraversion, etc., they rather reveal basic componential features (usually called "dimensions‟): activation level (high-low), activation slope (ascending-descending), source of regulation (endodynamic- exodynamic), phenomenal quality (endomodal-exomodal), and functionality (eufunctional vs. dysfunctional). The well-known Big-Five factors represent clusters of those features rather than simple dimensions. Sensation seeking, internalexternal control, i. e. further constructs of simple structure- oriented research, are likewise conceivable as patterns of functioning based on those five componential features. The validity of the five features obtained by varimin has largely been confirmed by rankings of the 30 NEO-PI-R facets using the features as judgmental criteria. Replacing Thurstonian simple structure by procedures aiming at complex structure might help to generate a systemic architecture in the personality and individual differences domains. More psychological functioning might be made transparent by modelling patterns of basic features.